The First Case of Acute Neonatal Suppurative Parotitis Caused by Escherichia coli in Korea - Jae Young Cho; Jong Hyuk Youn; Ji Sook Park; Jae Min Cho (Korean Society of Neonatology, 2020)
Neonatal acute suppurative parotitis is rare. Staphylococcus aureus is the most common pathogen and antibiotic treatment is the first line therapy. Here, we report a case of acute suppurative parotitis caused by Escherichia coli in a 7dayold male with febrile sensation, parotid swelling, and purulent discharge from the Stensen duct who was treated successfully with intravenous antibiotics. To the best of our knowledge, this is the first case of neonatal suppurative parotitis caused by E. coli in Korea.